The path not taken : French industrialization in the age of revolution, 1750-1830 - Horn, Jeff (Historian) (Transformations (M.I.T. Press), 2006)
Arguing that - contrary to Anglocentric accounts - French industrialization was not a failed imitation of the laissez-faire British model, but the product of a distinctive industrial policy that over the long-term led to prosperity comparable to Britain's, this text offers a comparison between the two approaches.